Interactive pragmatic skills of non-speaking children of 6–9 years old with autism spectrum disorder - Januszczak, Katarzyna (Logopedia Silesiana, 2020)
Although intensive research on autism has been conducted since the second half of the 20th century, the etiology of this disorder and the criteria for its diagnosis still raise many doubts. The available literature on the subject makes it possible to learn about the axial symptoms of autism spectrum disorders, in particular language difficulties, deficits in the sphere of social contacts as well as sensory disorders and motor mannerisms. The present paper presents the results of the research and analysis conducted for the PhD dissertation on the interactive skills of children with autism. The text describes the pragmatic, informational and emotional agility manifested in interactive behavior of autistic children aged 6-9 who cannot speak.